(NiSPOLNITEL_STWO AKADEMI^ESKOGO PENIQ(B.(NrEPERTUAR DLQ TENORA(B.s (NU^EBNO(B-(NMETODI^ESKOE POSOBIEs - (N|(B,(NtURSUNOWs; (N{(B,(NpIRMATOWs (NRECENZENTs; (Nm(B,(NrAZZAKOWAs (NRECENZENTs ((NtA[KENTs Musiqa, 2023)
(NdANNOE U^EBNO(B-(NMETODI^ESKOE POSOBIE PREDNAZNA^EN STUDENTAM WYS[IH U^EBNYH ZAWEDENIJ STUDENTAM wOKAL_NOE ISKUSSTWO(B((NAKADEMI^ESKOE PENIE(B)(NW OBLASTI MUZYKAL_NOGO ISKUSSTWA(B.s
Keywords: (NmETODIKAs